A Data-Driven Framework for the Accelerated Discovery of CO2 Reduction Electrocatalysts - Malek, Ali; Wang, Qianpu; Baumann, Stefan; Guillon, Olivier; Eikerling, Michael; Malek, Kourosh (Frontiers in Energy Research, 2021)
Searching for next-generation electrocatalyst materials for electrochemical energy technologies is a time-consuming and expensive process, even if it is enabled by high-throughput experimentation and extensive first-principle calculations. In particular, the development of more active, selective and stable electrocatalysts for the CO2 reduction reaction remains tedious and challenging. Here, we introduce a material recommendation and screening framework, and demonstrate its capabilities for certain classes of electrocatalyst materials for low or high-temperature CO2 reduction. The framework utilizes high-level technical targets, advanced data extraction, and categorization paths, and it recommends the most viable materials identified using data analytics and property-matching algorithms. Results reveal relevant correlations that govern catalyst performance under low and high-temperature conditions.